Personal income inequality and aggregate demand. (20th March 2015) - Carvalho, Laura; Rezai, Armon
Abstract : This paper presents a theoretical and empirical investigation of how changes in the size distribution of income can affect aggregate demand and the demand regime of an economy. After presenting empirical evidence for the US economy that the propensity to save increases significantly from the bottom to the top quintile of wage earners, we demonstrate that more equal distributions always lead to higher output in the traditional neo-Kaleckian macroeconomic model. We also present conditions under which a reduction of income inequality among workers results in demand becoming more wage led. This view is supported by the results of an econometric study for the USA (1967–2010), which show that the rise after 1980 in income inequality has made the US economy more profit led.